Within-tree variation in transpiration in isolated evergreen oak trees: evidence in support of the pipe model theory - Infante, Juan Manuel; Mauchamp, André; Fernández-Alés, Rocío; Joffre, Richard; Rambal, Serge (Tree Physiology, 2001)
Within-tree variation in sap flow density (SFD) was measured in two isolated evergreen oak (Quercus ilex L.) trees growing in an oak savannah (dehesa) in southwest Spain. Sap flow was estimated by the constant heating method. Three sensors were installed in the trunk of each tree in three orientations: northeast (NE), northwest (NW) and south (S). Sap flow density was monitored continuously from May 18 to September 27, 1993. Daily values of SFD ranged between 500 and 4500 mm3 mm−2 day−1. There were significant differences in SFD between orientations; SFD was higher in the NE and NW orientations than in the S orientation. These differences were noted on both a daily and seasonal time scale, and were less pronounced on cloudy days and at the end of the drought period, when SFD was relatively low. Our results support the idea that branches of trees can be viewed as a collection of small independent plants.
10.1093/treephys/21.6.409
Keywords: Dehesa; oak savannah; Quercus ilex; sap flow den- sity; water use